2018
DOI: 10.1177/1740774518792277
|View full text |Cite
|
Sign up to set email alerts
|

The ethics of uninsured participants accessing healthcare in biomedical research: A literature review

Abstract: Background/aims Sparse literature exists on the challenges and ethical considerations of including people with limited access to healthcare, such as the uninsured and low-income, in clinical research in high-income countries. However, many ethical issues should be considered with respect to working with uninsured and low-income participants in clinical research, including enrollment and retention, ancillary care, and post-trial responsibilities. Attention to the uninsured and low-income is particularly salient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 56 publications
(170 reference statements)
0
13
0
Order By: Relevance
“…At a minimum, the informed consent document and process should clearly present these additional costs of participation. As a matter of justice [27,28] and of scientific integrity, however, this is an insufficient solution. In the short term, health insurance could be provided to participants for their role, paid by either sponsoring pharmaceutical entities, institutions, and non-profit funders, or cost waivers or debt-forgiveness could be engineered by sites.…”
Section: Ancillary Costs Of Participationmentioning
confidence: 99%
“…At a minimum, the informed consent document and process should clearly present these additional costs of participation. As a matter of justice [27,28] and of scientific integrity, however, this is an insufficient solution. In the short term, health insurance could be provided to participants for their role, paid by either sponsoring pharmaceutical entities, institutions, and non-profit funders, or cost waivers or debt-forgiveness could be engineered by sites.…”
Section: Ancillary Costs Of Participationmentioning
confidence: 99%
“…In general, recruitment of depressed participants into clinical trials is difficult, and lower resourced individuals are not wellrepresented within these efforts. In the United States, large numbers of individuals from non-dominant cultures are underor uninsured, contributing barriers to health-related service receipt (Lillie-Blanton and Hoffman, 2005) as well as inclusion in clinical trials (Cho et al, 2018). Given the ubiquity of digital technologies, mobile health interventions increase intervention access for those who are traditionally missed (Anderson-Lewis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the debate of ancillary care is not limited to low-income countries: "research participants in high income countries who are uninsured or otherwise lack access to healthcare encounter limitations similar to those faced by participants in LMIC" [37]. In a literature review study of the ethics of uninsured participants accessing health care through research studies, Cho et al [37] examine the ancillary care debate in high-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, the debate of ancillary care is not limited to low-income countries: "research participants in high income countries who are uninsured or otherwise lack access to healthcare encounter limitations similar to those faced by participants in LMIC" [37]. In a literature review study of the ethics of uninsured participants accessing health care through research studies, Cho et al [37] examine the ancillary care debate in high-income countries. They found that some researchers assert that providing ancillary care could increase participants' misunderstanding of the purpose of research, expand occurrence of therapeutic misconception, and may serve as a potential disincentive for researchers to recruit from low-income communities [38].…”
Section: Introductionmentioning
confidence: 99%